Pemanfaatan Daun Mimba (Azadirachta indica) Sebagai Pestisida Nabati Dalam Mengatasi Masalah Hama di Desa Gondang Kecamatan Gangga Kabupaten Lombok Utara - Hidayah, Nurul; Rahma, Nita; Amelia, Rosana; Kumala, Restu; Meliandika, Ovy; Asmadi, Tobi (Universitas Mataram, 2024)
Gondang Village, Gangga District, North Lombok Regency, is one of the villages that utilizes land as an agricultural area and grows crops. The agricultural sector still has problems in agriculture such as plant pests and fertilizers used on these plants. Therefore, the use of appropriate botanical pesticides can overcome this problem. One of the plants that can be used as a botanical pesticide is the neem plant (Azadirachta indica) which has the potential to be a good botanical pesticide for food crops. Pest control using neem as a botanical pesticide has several advantages, namely the active compound is easily decomposed so the residue levels are relatively small, the method of action is specific so that it is safe for vertebrates (humans and livestock), and it is not easy to cause resistance, because the number of active compounds is more than one. With these advantages, agricultural products with excellent quality will be produced and ecosystem sustainability is maintained. The purpose of this activity is to utilize neem leaves as a botanical pesticide in overcoming plant pest problems in Gondang Village, North Lombok District. Therefore, the community can recognize and preserve the natural wealth and potential of the village.